The influence of intraoral devices in salivary cortisol levels of golf athletes : a pilot study - Cebola, Pedro (2019)
Abstract of the poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Campus Egas Moniz, Monte de Caparica, Portugal